Ca2+ and the regulation of small GTPases - Cullen, Peter (Henry Stewart Talks, 2007)
Introduction to small GTPases, Ras as a GTPase subfamily, Molecular entities, Ras GEFs and Ras GAPs, that couple Calcium to Ras activation, Temporal aspects of Calcium coupling to Ras activation, using the Calcium-regulated Ras GAPs CAPRI and RASAL as examples of amplitude and frequency Calcium sensors, Calcium as a messenger allowing Ras activation on endomembranes, Calcium coupling to Ras in physiology and disease
Archived at 2020/08/13